Applying ecosystem services principles to the derivation of freshwater environmental quality standards - Maltby, Lorraine; Brown, Ross; Wilkinson, Helen (Frontiers in Environmental Science, 2022)
Freshwater ecosystems provide many benefits to people (ecosystem services), but their biodiversity and functioning is threatened by anthropogenic stressors, including chemical pollution. Environmental quality standards (EQSs) for chemicals, are designed to protect species, but their derivation takes no account of ecosystem processes or species interactions and hence their links to biodiversity, ecosystem functioning and ecosystem services are uncertain. Here we explore a novel approach for the derivation of chemical EQSs to protect ecosystem service providing units (i.e., assemblages of species with ecological traits that underpin an ecosystem service) and ultimately protect ecosystem service delivery in different freshwater bodies and river basins. This approach, which was illustrated for two Water Framework Directive priority chemicals (a pyrethroid insecticide and polybrominated diphenyl ethers), is the first application of an ecosystem services framework to derive EQS values. The four-step approach enabled the derivation of ecosystem service-specific and river basin-specific standards that can inform spatially-defined and targeted management of chemical impacts on the aquatic (freshwater) environment. The derivation of ecosystem service specific EQS values also helps in communicating and highlighting the incremental benefits of improving water quality. A Tier I assessment focusing on protecting ecosystem service providing units was successfully undertaken based on available ecotoxicological effects data for each chemical. However, Tier II and Tier III assessments require further scientific research and tool development to quantify chemical impacts on ecosystem services delivery based on service providing taxa and their functional traits.